METHODS OF DEVELOPING SPEECH SKILLS IN A BILINGUAL ENVIRONMENT (USING THE EXAMPLE OF THE KARAKALPAK AND ENGLISH LANGUAGES): https://doi.org/10.5281/zenodo.15364381 - Matkarimova, D.A. (International scientific and practical conference, 2025)
In a period of increasing globalization and multiculturalism, bilingualism plays a pivotal role in personal and societal development. Developing speech skills in a bilingual environment, especially in regions like Karakalpakstan, where Karakalpak and English are the two primary languages, requires tailored educational approaches. This article explores effective methods of developing speech proficiency in bilingual learners, focusing on Karakalpak and English. It identifies key challenges such as language interference and limited practical exposure and suggests strategies like immersive learning, cultural integration, and technological tools to foster fluency. The study emphasizes the need for a balanced approach to bilingual education that nurtures both language skills in context and cultural awareness.